Reply to Comment by R. Parkinson on "Increasing Rates of Carbon Burial in Southwest Florida Coastal Wetlands" by J. Breithaupt et al. Issue 4 (6th April 2021) - Breithaupt, Joshua L.; Smoak, Joseph M.; Bianchi, Thomas S.; Vaughn, Derrick; Sanders, Christian J.; Radabaugh, Kara R.; Osland, Michael J.; Feher, Laura C.; Lynch, James C.; Cahoon, Donald R.; Anderson, Gordon H.; Whelan, Kevin R. T.; et al.
Abstract: Breithaupt et al. (2020, https://doi.org/10.1029/2019JG005349 ) investigated why rates of organic carbon (OC) burial in coastal wetlands appear to increase over the past ∼120 years. After comparing dating methods and applying biogeochemical analyses, we concluded that neither dating method nor carbon degradation contribute to the observed trend. Rather, we concluded that OC burial has increased in the past century. Parkinson's (2021) Comment disagrees with our conclusion, contending that: (1) use of a density correction to account for soil auto‐compaction is a flawed methodology that artificially shortens a core's length, (2) there is limited evidence for an acceleration in the regional sea‐level rise (SLR) rate, and (3) vertical accretion rates in previous papers by Breithaupt et al. (2014, https://doi.org/10.1002/2014JG002715 ; 2017, https://doi.org/10.1016/j.margeo.2017.07.002 ) are lower than the regional mean rate of SLR and are not to be believed as these wetlands should have converted to open water by now. We reject these contentions because: (1) no density correction was applied to the cores in this study, (2) local tide gauge records and analyses in the literature support an increase in SLR rates coinciding with the timeframe of our OC burial records, and (3) Parkinson's comparison of the 100‐yr mean rate of SLR neglects temporal variability and uncertainties in the long‐term sea‐level record, as well as biophysical feedbacks between wetland surface elevation and SLR. Here, we provide detailed responses to Parkinson's contentions and establish the importance of differentiating operational definitions of OC burial and accretion to clarify why an auto‐compaction correction is not applicable for OC burial measurements. Key Points: Organic carbon burial rates are not altered by auto‐compaction and do not include a density correction Increasing rates of sea‐level rise are supported by regional data and analyses from the literature